Правове регулювання в робототехніці - Турута, Олена Василівна (Гуманітарні аспекти цифрового суспільства : тези доп. учасників міжн. наук.-практ. конф. (Харків, 8 груд. 2022 р.), 2022)
The article analyses a feature that is very important for the legal perspective of the problem – it is a turn from understanding a robot as an entertainment product to the direction of development and research of social interaction between a robot and a human. The question is raised about the need to adopt new legal norms aimed at definition of “robot”, regulating the legal status of a robot, liability for damage caused by it, as well as legal problems of intellectual property associated with the functioning of robots.